Svalbard Imaginaries. The Making of an Arctic Archipelago - Albert, Mathias; Brode-Roger, Dina; Iversen, Lisbeth (Palgrave Macmillan, 2023)
Albert M, Brode-Roger D, Iversen L, eds. Svalbard Imaginaries. The Making of an Arctic Archipelago . Cham: Palgrave Macmillan; 2023.